2020
DOI: 10.1021/acs.est.0c01333
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Contribution of Crops to Nitrogen Pollution in the Yangtze River

Abstract: Agriculture contributes considerably to nitrogen (N) inputs to the world's rivers. In this study, we aim to improve our understanding of the contribution of different crops to N inputs to rivers. To this end, we developed a new model system by linking the MARINA 2.0 (Model to Assess River Input of Nutrient to seAs) and WOFOST (WOrld FOod STudy) models. We applied this linked model system to the Yangtze as an illustrative example. The N inputs to crops in the Yangtze River basin showed large spatial variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…From 1983 onwards, only N fertilizers were used in the catchment area of Yangtze. Recently, Chen et al [120] linked the MARINA 2.0 (Model to Assess River Input of Nutrient to seAs) and the WOFOST (WOrld FOod STudy) models to estimate the contribution of crop production systems to N enrichment of the Yangtze River and revealed that about 6,000 Gg of dissolved inorganic N originating from Yangtze basin entered the river in 2012. Half of this amount originated from the production of rice, wheat and vegetables to which N is supplied largely through mineral fertilizers.…”
Section: The Yangtze River Basin In Central Chinamentioning
confidence: 99%
“…From 1983 onwards, only N fertilizers were used in the catchment area of Yangtze. Recently, Chen et al [120] linked the MARINA 2.0 (Model to Assess River Input of Nutrient to seAs) and the WOFOST (WOrld FOod STudy) models to estimate the contribution of crop production systems to N enrichment of the Yangtze River and revealed that about 6,000 Gg of dissolved inorganic N originating from Yangtze basin entered the river in 2012. Half of this amount originated from the production of rice, wheat and vegetables to which N is supplied largely through mineral fertilizers.…”
Section: The Yangtze River Basin In Central Chinamentioning
confidence: 99%
“…The WOFOST model (de Wit et al 2020) was used to simulate maize production, being a well-known model that has been used in Zambia (Wolf et al 1987) as well as in regional and global studies (e.g., (Chen et al 2020;Droppers et al 2021;Wolf et al 2015)) including the derivation of the Global Yield Gap Atlas. Crop growth and production were simulated on a daily timestep as determined by crop type, soil type, hydrologic conditions, and weather (Van Diepen et al, 1989).…”
Section: Wofost Modelmentioning
confidence: 99%
“…Basin-scale nutrient export models are useful tools to understand the causes of nutrient exports from land to water systems, and to explore effective solutions (Chen et al, 2019a;Chen et al, 2020;Chen et al, 2019b;Kroeze et al, 2012;Li et al, 2019a;Li et al, 2017;Li et al, 2019b;Strokal et al, 2015;Strokal et al, 2016a;Strokal et al, 2016b;Wang et al, 2020a;Wang et al, 2019). Since the 1970s, basin-scale nutrient export models have been used to study water pollution and understand causes and effects at different scales.…”
Section: Modelling Nutrient Exports From Land To Lakes and Potential Impactsmentioning
confidence: 99%
“…However, the MARINA-Lakes model accounts for the most important processes associated with runoff, denitrification, river damming and water consumption. MARINA-Lakes is based on the existing modeling approaches that have been widely accepted and applied in China and other regions (Chen et al, 2019a;Chen et al, 2020;Chen et al, 2019b;Goshu et al, 2020;McCrackin et al, 2014;Strokal et al, 2016a;Wang et al, 2020a;Wang et al, 2019). The structure of the MARINA-Lakes model is transparent, facilitating implementation for future projections to assess the impact of management options on river export of nutrients to lakes.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation